2011
DOI: 10.1080/15504263.2011.570118
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Trial of Clozapine Versus Other Antipsychotics for Cannabis Use Disorder in Patients With Schizophrenia

Abstract: OBJECTIVE Cannabis use disorder is the most common co-occurring drug use disorder in people with schizophrenia and is associated with poor outcomes. We launched a randomized controlled trial to assess the impact of clozapine compared with treatment as usual on cannabis use in patients with schizophrenia and co-occurring cannabis use disorder. METHODS Thirty-one patients with schizophrenia and co-occurring cannabis use disorder were randomly assigned to switch to clozapine or to stay on their current antipsyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(27 citation statements)
references
References 70 publications
0
26
0
1
Order By: Relevance
“…The largest study included 95 patients with schizophrenia and comorbid substance use disorder in early remission, followed up to a decade, and found lower relapse rates for substance use in individuals treated with clozapine ( n = 25, 8%) than in those treated with other antipsychotics ( n = 70, 40%) ( P = 0.003) . A small randomized controlled trial in patients with comorbid schizophrenia and cannabis use disorder ( n = 31) showed a reduction in cannabis use among individuals randomized to clozapine for 12 weeks compared to other antipsychotics, equivalent to an effect size of 0.6 which did not reach statistical significance ( P = 0.086) .…”
Section: State Of the Artmentioning
confidence: 99%
“…The largest study included 95 patients with schizophrenia and comorbid substance use disorder in early remission, followed up to a decade, and found lower relapse rates for substance use in individuals treated with clozapine ( n = 25, 8%) than in those treated with other antipsychotics ( n = 70, 40%) ( P = 0.003) . A small randomized controlled trial in patients with comorbid schizophrenia and cannabis use disorder ( n = 31) showed a reduction in cannabis use among individuals randomized to clozapine for 12 weeks compared to other antipsychotics, equivalent to an effect size of 0.6 which did not reach statistical significance ( P = 0.086) .…”
Section: State Of the Artmentioning
confidence: 99%
“…Given tokens for cannabis‐free urine tests is currently under trial. The only pharmacological treatment that has had any success is clozapine: a double‐blind trial showed it to have a useful effect in diminishing craving for cannabis.…”
Section: Outcome and Treatmentmentioning
confidence: 99%
“…7 Furthermore, there is a need to examine the use of antipsychotic medication and investigate if some medications are particularly useful for patients with psychotic disorders who intend to continue to use cannabis. In a randomised trial comparing the effects of different antipsychotics, 8 clozapine seemed to stand out in reducing craving for cannabis, a finding that is in need of replication. Previous research has shown that stopping cannabis use after a first episode of psychosis has beneficial outcomes compared with continued use.…”
Section: Jorun Rugkåsamentioning
confidence: 99%